Cartilage Oligomeric Matrix Protein Associates With a Vulnerable Plaque Phenotype in Human Atherosclerotic Plaques. Issue 11 (November 2019) - Hultman, Karin; Edsfeldt, Andreas; Björkbacka, Harry; Dunér, Pontus; Sundius, Lena; Nitulescu, Mihaela; Persson, Ana; Boyle, Joseph J.; Nilsson, Jan; Hultgårdh-Nilsson, Anna; Bengtsson, Eva; Gonçalves, Isabel
Abstract : Background and Purpose—: Extracellular matrix proteins are important in atherosclerotic disease by influencing plaque stability and cellular behavior but also by regulating inflammation. COMP (cartilage oligomeric matrix protein) is present in healthy human arteries and expressed by smooth muscle cells. A recent study showed that transplantation of COMP-deficient bone marrow to apoE −/− mice increased atherosclerotic plaque formation, indicating a role for COMP also in bone marrow–derived cells. Despite the evidence of a role for COMP in murine atherosclerosis, knowledge is lacking about the role of COMP in human atherosclerotic disease. Methods—: In the present study, we investigated if COMP was associated with a stable or a vulnerable human atherosclerotic plaque phenotype by analyzing 211 carotid plaques for COMP expression using immunohistochemistry. Results—: Plaque area that stained positive for COMP was significantly larger in atherosclerotic plaques associated with symptoms (n=110) compared with asymptomatic plaques (n=101; 9.7% [4.7–14.3] versus 5.6% [2.8–9.8]; P =0.0002). COMP was positively associated with plaque lipids ( r =0.32; P =0.000002) and CD68 cells ( r =0.15; P =0.036) but was negatively associated with collagen ( r =−0.16; P =0.024), elastin ( r =−0.14; P =0.041), and smooth muscle cells ( r =−0.25; P =0.0002). COMP was positively associated with CD163 ( r =0.37; P =0.00000006), a scavenger receptor for hemoglobin/haptoglobin and a marker of Mhem macrophages, and with intraplaque hemorrhage, measured as glycophorin A staining ( r =0.28; P =0.00006). Conclusions—: The present study shows that COMP is associated to symptomatic carotid atherosclerosis, CD163-expressing cells, and a vulnerable atherosclerotic plaque phenotype in humans. Abstract : Supplemental Digital Content is available in the text.